Partisipasi Masyarakat dalam Pendidikan Al-Qur'an : Studi Kasus di Desa Sumatera Selatan - Rini Marlita; Nia Oktaviani (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyse community participation in the Qur’anic education of primary school-aged children in Lubuk Dendan Village, Mulak Sebingkai Sub-district. This study employs a qualitative approach using a case study design, with data collection techniques including observation, interviews and documentation. The results indicate that community participation in Qur’anic study sessions for primary school-aged children does exist, but is not yet optimal. Parents play a more dominant role in the form of indirect support, whilst direct involvement remains limited due to work commitments. Religious leaders have not yet been actively involved, whilst community leaders provide support through facilities and financial assistance, including the salaries of Qur’an teachers. Efforts to increase participation have been made through school policies requiring children to attend Qur’anic study sessions, as well as the imposition of sanctions. However, the level of participation achieved still tends to be influenced by external factors and does not yet stem entirely from community awareness. This study concludes that community participation in Qur’anic education for primary school-aged children in Lubuk Dendan Village is not yet optimal, as evidenced by the limited active involvement of the community and the predominance of indirect participation